Hermansky-Pudlak syndrome type 2: A rare cause of severe periodontitis in adolescents—A case study - Chen, Jun; Yang, Yifan; Liu, Binjie; Xie, Xiaoli; Li, Wenjie (Frontiers in Pediatrics, 2022)
Background and Aims: Hermansky-Pudlak syndrome (HPS) is an autosomal recessive disorder characterized by oculocutaneous albinism (OCA), platelet storage pool deficiency. The HPS-2 subtype is distinguished by neutropenia, and little is known about its periodontal phenotype in adolescents. AP3B1 is the causative gene for HPS-2. A Chinese 13-year-old girl presented to our department due to gingival bleeding and tooth mobility. Her dental history was otherwise unremarkable. Suspecting some systemic diseases as the underlying cause, the patient was referred for a medical consultation, a series of blood tests and genetic tests. In this case study, periodontal status and mutation screening of one HPS-2 case are presented. Methods: Blood analysis including a complete blood count (CBC) and glycated hemoglobin levels were measured. Platelet transmission electron microscopy (PTEM) was performed to observe the dense granules in platelets. Whole-exome sequencing (WES) and Sanger sequencing were performed to confirm the pathogenic variants. Results: A medical diagnosis of HPS-2 was assigned to the patient. Following the medical diagnosis, a periodontal diagnosis of “periodontitis as a manifestation of systemic disease” was assigned to the patient. We identified novel compound heterozygous variants in AP3B1 (NM_003664.4: exon7: c.763C>T: p.Q255*) and (NM_003664.4: exon1: c.53_56dup: p.E19Dfs*21) in this Chinese pedigree with HPS-2. Conclusion: This case study indicates the importance of periodontitis as a possible indicator of underlying systemic disease. Systemic disease screening is needed when a young patient presents with an unusual, severe periodontitis, as the oral condition may be the first of a systemic abnormality. Our work also expands the spectrum of AP3B1 mutations and further provides additional genetic testing information for other HPS-2 patients.